Photo De‐Mixing in Dion‐Jacobson 2D Mixed Halide Perovskites. Issue 26 (31st May 2022) - Wang, Ya‐Ru; Senocrate, Alessandro; Mladenović, Marko; Dučinskas, Algirdas; Kim, Gee Yeong; Rothlisberger, Ursula; Milić, Jovana V.; Moia, Davide; Grätzel, Michael; Maier, Joachim
Abstract: 2D halide perovskites feature a versatile structure, which not only enables the fine‐tuning of their optoelectronic properties but also makes them appealing as model systems to investigate the fundamental properties of hybrid perovskites. In this study, the authors analyze the changes in the optical absorption of 2D Dion‐Jacobson mixed halide perovskite thin films (encapsulated) based on (PDMA)Pb(I0.5 Br0.5 )4 (PDMA: 1, 4‐phenylenedimethanammonium spacer) exposed to a constant illumination. It is demonstrated that these 2D mixed‐halide perovskites undergo photo‐induced phase segregation, where the pristine mixed‐phase de‐mixes into iodide‐rich and bromide‐rich phases (photo de‐mixing). The de‐mixed state is largely maintained in the dark at room temperature for several months, while at higher temperatures it shows complete reversibility to the mixed‐phase in terms of optical and structural properties (dark re‐mixing). The authors further investigate temperature‐dependent absorption measurements under light to extract the photo de‐mixed compositions and to map the photo‐miscibility‐gap. This work thereby reveals that reversible photo de‐mixing occurs in Dion‐Jacobson 2D hybrid perovskites and provides strategies to address the role of light in the thermodynamic properties of these materials. Abstract : Thin films of 2D Dion‐Jacobson mixed halide perovskites undergo de‐mixing under light. In the dark, re‐mixing occurs with reversible recovery of the optical and structural properties. Based on temperature‐dependent absorption data after illumination, the de‐mixed phases' compositions (photo‐miscibility‐gap) are estimated using different methods.